Tolerance Fit Based Lubrication Clearance Design for Sliding Bearings in High Power Wind Turbine Gearboxes - Luo Yuan; Li Shengbo; Zhou Yinchun; Yuan Xiangfei; Hang Yulei; Savin·Leonid; Chen Zhaobo (Jixie chuandong)
The reasonable design of wind power sliding bearings is of particular importance in the increasingly widespread use of them in high-power wind turbine gearbox applications. The sliding bearing radial clearance (h0) is a significant parameter that reflects the sliding bearing's performance. It has a direct impact on bearing lubrication, load distribution, friction, vibration and other properties. Reasonable gap design not only ensures the normal functioning of the sliding bearing, but also enhances its operational efficiency and longevity. This study utilizes a sliding bearing in a high-power wind turbine gearbox to propose a lubrication clearance design method based on the tolerance fit, which takes into account factors such as roughness, trimming, and thermal deformation. Experimental research demonstrates that this method enables a reasonable configuration of the sliding bearing clearance, validating its correctness.